Hi, i'm currently stuck on an integration via substitution problem. I have an answer but the one given in the book of the book is different to mine. I'm wondering where exactly i've gone wrong, if i have: Q10: Integrate: x/ (x+1)^0.5 dx. Use the substitution, u^2 = x + 1. Heres my working: u^2 = x + 1. u = (x+1)^0.5 2u(du/dx) = 1 x = u^2 - 1 So, using some substitution: (u^2 - 1)/u 1dx (u^2 - 1)/u 2u(du/dx)dx (u^2 - 1)2 du (2u^2 - 2) du Now integrating with respect to u: (2/3)u^3 - 2u Substituting u = (x+1)^0.5 (2/3).(x+1)^1.5 - 2.(x+1)^0.5 However, the actual answer given in the back of the book is: (2/3)(x-2).(x+1)^0.5 Could anyone spot my mistake for me? Thanks a lot.